Sex-positive criminology - Wodda, Aimee (New directions in critical criminology, 2021)
Part one. Reducing harm, increasing agency -- Selling sex -- Institutional violence against those who sell sex -- Sexual education -- Reproductive justice -- Part two. Decriminalizing desire -- Carceral facilities -- BDSM and consent -- Young people's sexual identities and behaviors.